Wearable Walking Assistant for Freezing of Gait With Environmental IoT Monitoring: A Contribution to the Discussion - Bernardes, Rafael A.; Ventura, Filipa; Neves, Hugo; Fernandes, Maria Isabel; Sousa, Pedro (Frontiers in Public Health, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease, with a significant increase in the last three decades. Worldwide, seven to ten million people are affected by PD. In people living with PD, freezing of gait (FoG) has a great impact on activities of daily living, potentially leading to falls, injuries and loss of autonomy. FoG prevalence rates vary widely, reaching at least 50% of patients with PD. Current therapeutic options have limited effectiveness and their complement with innovative technology-based solutions in the real-world is demanded to enhance daily functioning for people living with PD. This article provides a narrative review on current technological developments for people living with PD and, derived from that evidence, presents a perspective on the integration of wearable technology and IoT to support telemonitoring and self-management of people living with PD in their daily living environment. Complementing current therapeutic options with technology-based solutions in PD patients' real-world environment is crucial to enhancing the quality of life of people living with PD. In that way, wearable technology and IoT might constitute resources of excellence towards seamless monitoring and self-management in peoples own home environment.